Presència valenciana al I Congrés Internacional de la Llengua Catalana (1906) - Ferrando, Antoni (Caplletra. Revista Internacional de Filologia, 2015)
This study of the Valencian representation at and contribution to the 1906 Conference discusses the failure of the Renaixença movement in Valencia.